2015
DOI: 10.1016/j.jvolgeores.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of mild strombolian activity on Mt. Etna

Abstract: 13Here we report the first measurements of gas masses released during a rare period of 14 strombolian activity at the Bocca Nuova crater, Mt. Etna, Sicily. UV camera data acquired for 15 195 events over a ≈ 27 minute period (27th July 2012) indicate erupted SO 2 masses ranging 16 from ≈ 0.1 to ≈ 14 kg per event, with corresponding total gas masses of ≈ 0.1 to 74 kg. Thus, 17 the activity was characterised by more frequent and smaller events than typically associated 18 with strombolian activity on volcanoes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 46 publications
7
41
0
Order By: Relevance
“…Whilst the UV imaging of ash rich plumes has been acheived, yielding interesting insights into ash phase plume dynamics [48], the reduction in optical thickness caused by ash in these cases rules out the retrieval of SO 2 emissions. Interestingly, these explosive UV camera studies typically point toward the non-explosive release of gas as being the dominant means by which these volcanoes release volatiles to the atmosphere [21,[49][50][51][52][53][54], especially for basaltic open conduit cases, such as Etna and Stromboli in Italy, where gas bubbles are free to move through the melt. Indeed, in the Stromboli case, degassing was partitioned as 77% passive gas release (e.g., from spherical bubbles), 16% from puffing, e.g., from cap bubbles, and with only 7% from explosions, e.g., from gas slugs (Taylor bubbles) [49].…”
Section: Improving the Spatio-temporal Resolution Of Volcanic Degassingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the UV imaging of ash rich plumes has been acheived, yielding interesting insights into ash phase plume dynamics [48], the reduction in optical thickness caused by ash in these cases rules out the retrieval of SO 2 emissions. Interestingly, these explosive UV camera studies typically point toward the non-explosive release of gas as being the dominant means by which these volcanoes release volatiles to the atmosphere [21,[49][50][51][52][53][54], especially for basaltic open conduit cases, such as Etna and Stromboli in Italy, where gas bubbles are free to move through the melt. Indeed, in the Stromboli case, degassing was partitioned as 77% passive gas release (e.g., from spherical bubbles), 16% from puffing, e.g., from cap bubbles, and with only 7% from explosions, e.g., from gas slugs (Taylor bubbles) [49].…”
Section: Improving the Spatio-temporal Resolution Of Volcanic Degassingmentioning
confidence: 99%
“…Furthermore, during a study of rapid (0.25 Hz) strombolian activity on Mt. Etna, explosive data were plotted on a scatter plot of repose time following the event vs. event mass [51]. An absence of large mass, long repose time data were noted, which was interpreted as being due to coalescence of adjacent rising slugs, e.g., leading to a longer repose interval before the arrival of the next distinct slug, and constituting the first direct empirical evidence of slug interaction in volcanic conduits.…”
Section: Combination Of Uv Camera Degassing Data With Geophysical Datmentioning
confidence: 99%
“…Whilst UV imaging of ash rich plumes has been acheived, yielding interesting insights into the ash phase plume dynamics [46], the reduction in optical thickness caused by ash in these cases, rules out retrieval of SO2 emissions. Interestingly, these explosive UV camera studies typically point towards non-explosive release of gas as being the dominant means by which these volcanoes release volatiles to the atmosphere [21,[47][48][49][50][51][52], especially for basaltic open conduit cases, such as Etna and Stromboli, where gas bubbles are free to move through the melt. In particular, Tamburello et al [47] reported that, for Stromboli volcano, degassing was partitioned as 77% passive gas release (e.g., from spherical bubbles), 16% from puffing, e.g., from cap bubbles and with only 7% from explosions, e.g., from gas slugs (Taylor bubbles).…”
Section: Improving Spatio-temporal Resolution Of Volcanic Degassingmentioning
confidence: 99%
“…Furthermore, during a study of rapid (0.25 Hz) strombolian activity on Mt. Etna, explosive data were plotted on a scatter plot of repose time following the event vs. event mass [49]. An absence of large mass, long repose time data were noted, which was interpreted as being due to coalescence of adjacent rising slugs, e.g., leading to a longer repose interval before the arrival of the next distinct slug, and constituting the first direct empirical evidence of slug interaction in volcanic conduits.…”
Section: Combination Of Uv Camera Degassing Data With Geophysical Datmentioning
confidence: 99%
“…Combining geophysical and degassing data in this way provides scope for a far more holistic system understanding than a discrete analysis of the individual datasets, as first demonstrated on such time frames using spectroscopic gas flux data [20]. In addition, these high temporal resolution data enable a comparison against mathematical and numerical models of underground gas flow processes, providing new insights into the subterranean fluid dynamics, which drive surficial activity [8,21,22]. Much attention has also been directed towards scrutinising the data processing routines and considering sources of error in SO 2 camera retrievals (e.g., [8,[23][24][25][26][27]), related to light dilution, plume speed determination, and the calibration procedure.…”
Section: Introductionmentioning
confidence: 99%